Weakening of hurricanes via marine cloud brightening (MCB) - Latham, John; Parkes, Ben; Gadian, Alan; Salter, Stephen (Atmospheric science letters, 2012)
This paper examines the potential to cool ocean surface waters in regions of hurricane genesis and early development. This would be achieved by seeding, with copious quantities of seawater cloud condensation nuclei (CCN), low‐level maritime stratocumulus clouds covering these regions or those at the source of incoming currents. Higher cloud droplet density would increase these clouds' reflectivity to incoming sunlight, and possibly their longevity. This approach is therefore a more localized application of the marine cloud brightening (MCB) geoengineering technique promoting global cooling. By utilizing a climate ocean/atmosphere coupled model, HadGEM1, we demonstrate that—subject to the satisfactory resolution of defined but unresolved issues—judicious seeding of maritime stratocumulus clouds might significantly reduce sea surface temperatures (SSTs) in regions where hurricanes develop. Thus artificial seeding may reduce hurricane intensity; but how well the magnitude of this effect could be controlled is yet to be determined. We also address the important question as to how MCB seeding may influence precipitation. GCM modelling indicates that the influence of seeding on undesirable rainfall reductions depends on its location and magnitude. Much more work on this topic is required. Copyright © 2012 Royal Meteorological Society